2021
DOI: 10.51248/.v41i1.528
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel potent pancreatic lipase inhibitors from Ficus racemosa

Abstract: Introduction and Aim: Obesity is a disorder of lipid metabolism and continues to be a global problem, ranking fifth for deaths worldwide. It is considered to be main reason for a number of physiological changes that resulting in many metabolic disorders such as cardiovascular diseases, diabetes, musculoskeletal disorders and various cancer types. Obesity develops from long-termed physiological imbalances in energy expenditure.. One of the therapeutic strategies in managing obesity is inhibition of pancreatic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The relationship between an increase in extracellular dopamine and NF-κB activation and inflammation reveals certain intracellular targets that may be exploited to discover novel targets in colon cancer cells for effective treatment strategies. Our results are concordant with the previous studies [25][26][27]. DA was shown to reduce tumor growth, metastasis, and tumor angiogenesis [25].…”
Section: Discussionsupporting
confidence: 93%
“…The relationship between an increase in extracellular dopamine and NF-κB activation and inflammation reveals certain intracellular targets that may be exploited to discover novel targets in colon cancer cells for effective treatment strategies. Our results are concordant with the previous studies [25][26][27]. DA was shown to reduce tumor growth, metastasis, and tumor angiogenesis [25].…”
Section: Discussionsupporting
confidence: 93%
“…The lipase inhibitory activity exhibited by CFL-AuNPs was higher than that of CFLE, which had a maximum inhibitory activity of 33.44 ± 0.93%. Similarly, Anand et al [52] reported the in vitro lipase inhibitory activities of Ficus racemosa extract. The aqueous extract showed prominent pancreatic lipase inhibitory potential in a dose-dependent manner, ranging from 12 to 46%, with maximum inhibitory activity at a concentration of 25 µg/ml.…”
Section: Anti-obesity Activity Of Cfl-aunpsmentioning
confidence: 92%
“…When bacteria develop resistance to an antibiotic, they can either horizontally or vertically transfer this trait to their offspring. These days, new resistant bacterial strains that are somewhat more deadly than the original strain have emerged as a result of the indiscriminate and illogical use of antibiotics (Chandra et al, 2017;Anand et al, 2021) Over the world, medicinal plants have been used to cure a variety of illnesses caused by bacteria. Many chemical compounds having pharmacological uses can be found in medicinal plants.…”
Section: Introductionmentioning
confidence: 99%